Rethinking Leadership for a Green World - Taylor, Andrew, 1972- (London ; New York : Routledge Taylor & Francis Group, 2022)
"First James Lovelock, and recently Prince William and David Attenborough believe that we have reached a tipping point in the process of climate change. Whether they are right, or not, it is certainly true that the impact of humankind upon the ecology of the earth has reached a point where real changes in human behaviour are required. If managers are to be enablers of planetary survival then we need to develop a new approach to risk, which explicitly includes ecological limits upon economic behaviour. This implies a fundamental reorientation of their role in allocating resources to minimise risk and maximise reward. This book brings together some of the brightest contemporary thinkers on leadership, complexity and sustainability to consider the big ideas that we will need to make the changes required, and to outline the major themes that can inform a new approach to constructing a green world. It looks at how to ensure that local models of sustainability are able to flourish in the context of global networks and presents specific case studies of markets and organisations that offer insights into the development integrated solutions and the leadership lessons we can learn. Combining both theory and practice, this book serves to guide business managers and provides deeper insight and critical perspectives on some of the key issues facing leaders moving towards the green economy. It also provides useful supplementary reading for students in business and environmental studies"--
Includes bibliographical references and index.
Keywords: Leadership; Climatic changes -- Social aspects; Climatic changes -- Political aspects